Biological Asset Disclosure, Profitability, and Green Accounting: The Impact on Company Value - Harvanda, Veriza Norma; Zandra, Rosy Aprieza Puspita; Miharso, Apit; Prasetya, Rizky (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
This research aimed to determine the impact of biological assets disclosure measured by using index Wallace, profitability measured by return on assets (ROA), and green accounting expressed by PROPER, on firm value, measured by using Tobin’s Q. The data used in this study were analyzed by using multiple linier regression. The population for this research comprised agricultural companies listed on the ISE between 2016 and 2022. The research sample was selected using a purposive sampling method, resulting in a total of 7 companies. The results of this research partially showed that the biological assets disclosure and profitability had a positive effect on the firm value. Meanwhile, green accounting had no effect on firm value. Simultaneously, biological assets disclosure, profitability, and green accounting had an impact on firm value. The novelty of this research lies in its comprehensive analysis of the interplay between biological asset disclosure, profitability, and green accounting practices on firm value within the agricultural sector, emphasizing the importance of adhering to PSAK 69 for biological assets disclosure. Companies should focus on improving biological assets disclosure and profitability by increasing revenue and reducing costs to enhance firm value.